2012
DOI: 10.1007/s11427-012-4354-3
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic changes associated with oocyte aging

Abstract: It is well established that the decline in female reproductive outcomes is related to postovulatory aging of oocytes and advanced maternal age. Poor oocyte quality is correlated with compromised genetic integrity and epigenetic changes during the oocyte aging process. Here, we review the epigenetic alterations, mainly focused on DNA methylation, histone acetylation and methylation associated with postovulatory oocyte aging as well as advanced maternal age. Furthermore, we address the underlying epigenetic mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 65 publications
0
21
0
1
Order By: Relevance
“…In this review, we introduced ideas about abnormal lysine acetylation associated with postovulatory oocyte aging and the roles of HDACs in oocyte and embryos. Abnormal histone acetylation and DNA methylation of oocytes are also associated with advanced maternal age [9]. Thus, the epigenetic status of oocytes is not static, but rather dynamic, and easily changes with aging, possibly affecting the developmental potential of embryos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, we introduced ideas about abnormal lysine acetylation associated with postovulatory oocyte aging and the roles of HDACs in oocyte and embryos. Abnormal histone acetylation and DNA methylation of oocytes are also associated with advanced maternal age [9]. Thus, the epigenetic status of oocytes is not static, but rather dynamic, and easily changes with aging, possibly affecting the developmental potential of embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, it has been reported that the epigenetic alterations including DNA methylation and histone acetylation are also associated with postovulatory aging [9]. DNA methylation is involved in transcriptional repression, X chromosome inactivation and genomic imprinting [10].…”
Section: Introductionmentioning
confidence: 99%
“…; Liang et al . ). Failed and abnormal fertilization is frequently observed in aged oocytes, and could result in poor embryo development and early pregnancy loss (Fujino et al .…”
Section: Introductionmentioning
confidence: 97%
“…Oocyte aging rapidly decreases their quality and capacity to undergo embryonic development after fertilization. Functional and morphological changes associated with oocyte aging include decreased fertilization rates, polyspermy, parthenogenetic activation, apoptosis, chromosomal abnormalities, cortical granules exocytosis, ooplasmic microtubule dynamics, zona pellucida hardening, decreases in MPF and MAPK activities, epigenetic changes, and abnormal or delayed embryo development [24,[68][69][70][71]. Pathological conditions of oocyte aging impose limits for assisted reproduction technologies in animals as well as in humans [72].…”
Section: No Effects On Oocyte Agingmentioning
confidence: 99%